2008
DOI: 10.1051/0004-6361:200810174
|View full text |Cite
|
Sign up to set email alerts
|

High precision radial velocity measurements in the infrared

Abstract: High precision radial velocity (RV) measurements in the near infrared are in high demand, especially in the context of exoplanet search campaigns shifting their interest to late type stars in order to detect planets with ever lower mass or targeting embedded pre-main-sequence objects. ESO commissioned a new spectrograph at the VLT -CRIRES -designed for high resolution near-infrared spectroscopy with a comparably broad wavelength coverage and the possibility of using gascells to provide a stable RV zero-point. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…This procedure allowed for a correction of the systematics still present in the data after our first reduction. Seifahrt & Käufl (2008), a contemporary study, reached a precision of 20 m/s on one night. A dedicated effort was made to track systematics and understand their possible causes.…”
Section: Discussionmentioning
confidence: 94%
“…This procedure allowed for a correction of the systematics still present in the data after our first reduction. Seifahrt & Käufl (2008), a contemporary study, reached a precision of 20 m/s on one night. A dedicated effort was made to track systematics and understand their possible causes.…”
Section: Discussionmentioning
confidence: 94%
“…A similar strategy for wavelength calibration is the use of telluric lines in the NIR as a natural gas cell. In the observations, the telluric lines are superimposed on the stellar spectra, and Seifahrt et al (2008) showed that these atmospheric lines are stable in terms of velocity in the order of 10 m s −1 . Figueira et al (2010) adopted telluric lines as a stable wavelength reference, and showed that these lines allow us to reach RV precisions that are even better than 10 m s −1 when accounting for the changing weather conditions at the observatory during the observations.…”
Section: Instrumental Limitationsmentioning
confidence: 99%
“…The RV of the telluric lines is constant in all wavelengths down to a level of 10 m s −1 (e.g., Figueira et al 2010;Seifahrt & Käufl 2008), which is about a magnitude smaller than the velocity precision we can achieve with NIRSPEC. The basics of the self-calibration method have been extensively described (e.g.…”
Section: Relative Radial Velocity Methodsmentioning
confidence: 64%